Finerenone and Clinical Outcomes in CKD and Type 2 Diabetes by Frailty Index. FIDELITY Post Hoc Analysis (2025)
Background Frailty is associated with a higher risk of adverse outcomes. It is believed that people with a higher frailty index (FI) may be less tolerant to new treatments, often leading to inappropriate prescribing. This post hoc analysis of FInerenone in chronic kiDney diseasE and type 2 diabetes: Combined FInerenone in reducing kiDnEy faiLure and dIsease prOgression in Diabetic Kidney Disease (FIDELIO-DKD) and FIGARO-DKD Trial program analysis, a prespecified, pooled analysis of the FIDELIO-DKD and FIGARO-DKD phase 3 clinical trials, investigated the efficacy and safety of finerenone versus placebo according to baseline FI. Methods Between September 2015 and October 2018, 12,990 people with CKD and type 2 diabetes receiving the maximum tolerated dose of a renin-angiotensin system inhibitor were randomized to receive finerenone 10 or 20 mg once daily or placebo. Baseline FI was calculated using the Rockwood cumulative deficit approach including 30 clinical characteristics. Primary efficacy outcomes included a kidney (kidney failure, sustained decrease of $57% in eGFR, or kidney-related death) and a cardiovascular (CV) composite outcome (CV death, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for heart failure). Changes in urine albumin-to-creatinine ratio and eGFR were measured across the study period. Results Overall, kidney and CV event rates increased with increasing frailty. Finerenone reduced the risk of primary kidney and CV composite outcomes irrespective of baseline frailty (P interaction 5 0.93 and 0.35, respectively). Compared with placebo, finerenone also demonstrated significant reductions in urine albumin-to-creatinine ratio across all frailty subgroups (P , 0.01 for all visits) and significant attenuation of eGFR decline from baseline to month 48 in the three most frail quartiles (.Q1 to #Q2, P 5 0.001; .Q2 to #Q3, P , 0.001; .Q3, P , 0.001, respectively). The incidence of serious adverse events and hyperkalemia increased with increasing frailty in both treatment arms. Conclusions Finerenone reduced the risk of CV and kidney events in people with CKD and type 2 diabetes versus placebo irrespective of baseline frailty status.